Sulfuric Acid Functionalized Silica-Coated Magnetic Nanoparticles: Preparation and Application in Synthesis of Mono-, Di- and Tri[bis(6-aminopyrimidinyl)methanes] - Karimi, Ali Reza; Dalirnasab, Zeinab; Karimi, Marzie; Bagherian, Fatemeh (Synthesis, 2013)
Sulfuric acid functionalized silica-coated magnetic nanoparticles (SSA-MNPs) were prepared by a simple method and evaluated as efficient catalysts for the condensation reaction of 6-amino-1,3-dimethyluracil with mono-, di-, or trialdehydes to give the corresponding mono-, di- and tri[bis(6-aminopyrimidinyl)methanes]. The catalyst was simply recycled by the use of an external magnetic field and could be reused five times without significant loss of activity or mass.
Keywords: nanostructures; catalysis; condensation; aldehydes; heterocycles; ultrasound